2010
DOI: 10.1109/tap.2010.2041143
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Wave Propagation Into Large Building Structures—Part 2: Characterization of Multipath

Abstract: We report on measurements that characterize multipath conditions that affect broadband wireless communications in building penetration scenarios. Measurements carried out in various large structures quantify both radio-signal attenuation and distortion (multipath) in the radio propagation channel. Our study includes measurements of the complex, wideband channel transfer function and bandpass measurements of a 20 MHz-wide, digitally modulated signal. From these, we derive the more compact metrics of time delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Several projects in NIST s Public Safety Communications Research Laboratory have been funded by the Department of Justice s Community-Oriented Policing Services (COPS) program; these include work described in [31] and [36]- [40]. The site-and frequency-diversity results of this paper are a continuation of this work.…”
Section: Large-scale Site and Frequency Diversity Inmentioning
confidence: 99%
“…Several projects in NIST s Public Safety Communications Research Laboratory have been funded by the Department of Justice s Community-Oriented Policing Services (COPS) program; these include work described in [31] and [36]- [40]. The site-and frequency-diversity results of this paper are a continuation of this work.…”
Section: Large-scale Site and Frequency Diversity Inmentioning
confidence: 99%
“…The sampling of RSS values is a time consuming effort that requires a lot of time hence it can be avoided by the modeling of radio signals in indoor environment. There were many efforts made to effectively model the radio signal propagation in indoor environment but it is not getting the required accuracy, mainly because of the obstacles, multipath, reflection, and scattering issues [1]. Even fingerprinting is also proved inaccurate as it introduces noticeable error due to the changes in indoor environment, building layout, activity of the people inside, furniture and other stuff, these changes and modification are not easy to be addressed in indoor propagation models [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an experiment by [9] to estimate the effects of multipath on "chaotic radio" pulse tests were conducted in corridors with dimensions of 4 m × 40 m × 3 m and conference halls of 20 m × 4 m × 16 m by varying the distance between the transmitter and receiver from 1 -20 m. After conducting these tests in these various environments, their results showed that the effect of multipath interference on their signal was negligible. In [10] multipath effects are measured in various large environments such as a multi-story apartment building, an oil refinery, a long corridor in an office building typical of many commercial facilities, and a subterranean tunnel, to characterize the risk of BER to emergency responders.…”
Section: Prior Work Experimental Setupsmentioning
confidence: 99%